2022
DOI: 10.1186/s12888-022-04140-6
|View full text |Cite
|
Sign up to set email alerts
|

A Southeast Asian expert consensus on the management of major depressive disorder with suicidal behavior in adults under 65 years of age

Abstract: Background The high prevalence of suicidal behavior among individuals with major depressive disorder (MDD) in Southeast Asia (SEA) underscores the need for optimized management to address depressive symptoms, reduce suicide risk and prevent suicide in these individuals. Given the lack of clear guideline recommendations for assessing and managing these patients, regional consensus-based recommendations which take into account diverse local contexts across SEA may provide useful guidance for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In Indonesia, depression is ranked as one of the leading causes of disability-adjusted life years (ref). Currently, there are still unmet needs in the assessment and treatment of individuals with depression and SI 7. Moreover, studies identified specific cultural and social risk factors for suicide in Southeast Asia, such as the level of religious involvement and severity of interpersonal problems 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, depression is ranked as one of the leading causes of disability-adjusted life years (ref). Currently, there are still unmet needs in the assessment and treatment of individuals with depression and SI 7. Moreover, studies identified specific cultural and social risk factors for suicide in Southeast Asia, such as the level of religious involvement and severity of interpersonal problems 8.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are still unmet needs in the assessment and treatment of individuals with depression and SI. 7 Moreover, studies identified specific cultural and social risk factors for suicide in Southeast Asia, such as the level of religious involvement and severity of interpersonal problems. 8 Also, compared with high-income countries (HICs), the male-to-female ratio for suicide is closer to 1, 2 and the overall reported prevalence of mental health conditions is lower in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the estimated prevalence of SA in patients with MDD is 23.7% [3], highlighting the strong need for early detection and intervention of SA among these patients. Numerous studies have identi ed some risk factors for SA in patients with MDD, such as gender [4], genetic factors [5,6], substance use [7,8], stressful life events [9,10], and anxiety [11,12].…”
Section: Introductionmentioning
confidence: 99%